Bond Market Development in Developing Asia - John D. Burger; Francis E. Warnock; Veronica Cacdac Warnock (Asian Development Bank (ADB), 2015)
We describe and assess two dimensions of the current state of bond market development in developing Asia: the role of bond markets in overall financial systems and a comparison of the salient features of bond market development in developing Asia and other regions. We highlight key drivers and constraints of bond market development in developing Asia, particularly in smaller economies, as well as key implications for policymakers, especially for promoting bond market development in the region. Our analysis suggests that high inflation volatility presents a serious obstacle to bond market development. We find that smaller developing Asian economies could enable bond market development by pursuing creditor friendly policies and strengthening the legal rights of borrowers.
hdl:11540/5131
Keywords: G10; G15; F30; 330; bond market; financial development; financial system